AB0279 Periodontal Disease and Rheumatoid Arthritis – Comparison of Two Assessment Tools, and Their Value in The Determination of The Association between The Two Diseases - Bocskai, M.; Zalai, Z.; Antal, M.; Braunitzer, G.; Kovács, L. (Annals of the rheumatic diseases, 2016)
BackgroundPeriodontitis is involved in the pathogenesis of rheumatoid arthritis (RA), and a worse periodontal status has been proposed to correlate with the inflammatory activity of RA and to have an impact on its responsiveness to therapy. Human studies have been hampered by the lack of well-standardized assessment tools of the severity of periodontal disease (PD).ObjectivesThe authors' aim was to compare the accuracy of two scoring systems of PD in RA patients, and to correlate the findings with multiple variables of RA activity and severity.MethodsEighty-one RA patients (mean age: 57 years, range: 28–82) were consecutively recruited. Disease activity was measured with DAS28, ESR, CRP, and swolllen and tender joint counts. Disease severity was assessed by the health assessment questionnaire (HAQ), anti-citrullinated peptide (mutated citrullinated vimentin) antibody and rheumatoid factor titers, and average DAS28 and average corticosteroid dose in the preceding year. The scoring of the severity of PD was assessed by means of the Community Periodontal Index of Treatment Needs (CPI) and the periodontal status classification, proposed by Fernandes et al. CPI scores PD severity on a 0–4 scale according to the presence of calculus and bleeding on probing (BOP) and probing depth, whereas the other index categorizes the severity as healthy-early-moderate-severe on the basis of clinical attachment level (CAL) and probing depth. Smoking status was also recorded.ResultsRA patients had a median score of 3 on the CPI index, and the median severity was moderate according to the periodontal status scale. The two systems had excellent correlation (Spearman r=0,966, p<0.0001), and there was also a negative correlation between the number of teeth and the CPI score (r=0,254, p<0.05) and the periodontal status score (r=0,210, p=0.059). A worse periodontal status (assessed with higher CPI score) was associated with a higher average DAS28 (despite therapy) measured during the year before the dental examination (r=0,376, p=0,022), with smoking (Kruskal-Wallis: p=0.014), and with higher DAS28 at the time of the examination (r=0.198, p=0.07). When assessed with the 4 staged periodontal status score, the association between PD severity and current DAS28 was significant (r=0.409, p=0.01).ConclusionsCPI seems to have better performance than the periodontal status score proposed by Fernandes et al for the examination of the severity of PD in RA patients, and confirms the correlation between the severity of PD and RA activity and severity. This method is recommended for the research on the impact of periodontal status and of its correction on RA outcome.Disclosure of InterestNone declared